PENGEMBANGAN KESADARAN HUKUM MASYARAKAT DESA BUKIT LAYANG KECAMATAN BAKAM KABUPATEN BANGKA - Toni Toni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2015)
The implementation of this community service aims to become a facilitator between village officials and the community in identifying problems faced by the village related to the community, providing suggestions for alternative legal solutions in the village and providing ideas for understanding the law to the community in accordance with the scientific field that has been owned. The methods used are socialization of laws and regulations, discussions, training and visits to people's homes. With all the advantages and disadvantages, it is hoped that this work program can be useful for students and the Bukit Layang Village community and can be a stimulant for developing legal awareness for the village community.